Knowledge on pulmonary tuberculosis among Dalit community of Bharatpokhari VDC of Kaski district, Nepal - Lamichhane, Rajendra; Marasini, Nabin Raj; Lama, Nishant; Subedi, Sangam; Marasini, Nirmal Raj (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis still remains public health problems in Nepal. Previous studies among marginalized ethnic groups suggest that being poor increases the risk of tuberculosis. Dalit communities are those communities in Nepal, backward in social, economic and educational fields and are not excluded from the risk of tuberculosis. The objective of the study was to determine the level of knowledge on pulmonary tuberculosis among Dalit community of Bharatpokhari VDC of Kaski. Methods: Community based cross-sectional study was conducted to determine the level of knowledge on pulmonary tuberculosis among Dalit community of Bharatpokhari VDC, Kaski from January 2010 to July 2010. Samples were taken randomly from different wards of the VDC. Data was collected by using pretested structured questionnaire by home to home visit of age 15-49 years. Data was collected from 15th January 2010 to 15th May 2010. Results: Study revealed that 29% respondents had adequate level of knowledge on pulmonary tuberculosis. The factor, education status was associated with level of knowledge on pulmonary tuberculosis on bivariate analysis (p=0.005). Conclusions: More than two third of the respondents had inadequate level of knowledge on pulmonary tuberculosis. Thus, recommends for the awareness programme on pulmonary tuberculosis. The education status and level of knowledge on pulmonary tuberculosis was significantly associated on bivariate analysis, and recommends for improvement in the education status of dalit community would be beneficial.